رضا المرضى عن جودة الخدمات الصحية في المستشفيات الفلسطينية (خدمات التغذية و خدمات النظافة نماذج لدراسة مقارنة بين مستشفي الشفاء وغزة الأوروبي) - Aamer Suliman Abu Shariaa; Zulkiple Abd.Ghani; Muhamad Yusuf Khalid; Mosbah Mansour Motawea; Yehia Awad Abed (Universiti Sains Islam Malaysia, 2024)
The study aimed to see patients' satisfaction with the quality of health services especially hotel services, including whether the services of a hotel is equally important for all patients, see the strengths and weaknesses of these services, suggestion priorities for improvement and to provide data make recommendations to officials for proper planning for these services. The descriptive analysis which consists frequencies, percentages, means and standard deviation was used adopting (SPSS), the researcher used Likert scale. The study found that patients 'satisfaction with the quality of nutrition services at Shifa Hospital is better than their satisfaction with the quality of nutrition services in the European Gaza Hospital. The study also found that satisfaction with the quality of cleaning services did not reach the minimum required, particularly with regard to the provision of cleaning materials, but the level of satisfaction with the quality of cleaning services in the European hospital slightly better than the case at Shifa hospital.